Comprehensive cardiopulmonary profile of individuals with Down syndrome. Issue 12 (23rd June 2022) - Beck, V. D. Y.; Wee, S. O.; Lefferts, E. C.; Hibner, B. A.; Burton, L. C.; Baynard, T.; Fernhall, B.; Hilgenkamp, T. I. M.
Abstract: Background: Individuals with Down syndrome (DS) have low levels of cardiorespiratory fitness and previous studies have shown that these low levels of fitness have a physiological cause. During exercise, the cardiovascular, ventilatory and muscular systems are simultaneously active. While individual parameters of these systems have been investigated in DS before, the interaction between these parameters and systems have not been discussed in detail. Doing so may provide important insight regarding the aetiology of low cardiorespiratory fitness and which parameters of the cardiovascular, pulmonary and muscular systems are altered in individuals with DS compared with their peers without DS. Methods: Cardiopulmonary exercise tests were performed in healthy adults with and without DS. Parameters related to the cardiovascular, ventilatory and muscular systems were collected until VO2peak . In total, 51 participants were included in analysis, of which 21 had DS. Results: Individuals with DS showed lower peak values for all collected outcomes ( P ≤ 0.001) compared with those without DS, except for ventilatory threshold as a percentage of maximal oxygen uptake and VE /VCO2 slope, which were similar. Conclusions: Our results show that individuals with DS present impairments across the cardiovascular, ventilatory and muscular aspects of the cardiopulmonary system.